RETRACTED: Estimation of growth rates of Acipenser persicus Borodin, 1897 in cage farming conditions and in a water recycling facility - Milovanov Ivan; Kovalenko Matvey; Rikhavi Adnan; Paly Dinara; Sorokina Marina; Firsova Angelina; Shikhshabekova Basiyat (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001